ANALISIS KINERJA KEUANGAN DAN BIAYA LINGKUNGAN PADA PT HARUM ENERGY TBK PERIODE 2019 – 2023 - Wulandari, Anak Agung Ayu Intan; Dewi, Gita Apsari; Krisnadewi, Komang Urip (Komunitas Manajemen Kompetitif, 2025)
Abstract: The assessment of a company's financial level can be done by analyzing the company's financial statements. The analysis conducted can be done using ratio analysis. The purpose of this research is to determine the financial performance of PT Harum Energy Tbk in terms of financial ratio analysis. The analysis method used is descriptive quantitative analysis using profitability ratio and environmental cost ratio measurements. Data and information for the research were obtained from the annual report of PT Harum Energy Tbk listed on the IDX. Based on the research results, the profitability ratio has fluctuated but remains above the required ratio, indicating that the financial performance is classified as good. In the environmental cost ratio, there are also fluctuations, but in terms of environmental performance, it is still considered good. This can be seen from the environmental performance awards received from 2019-2023.